Peran ekstrakurikuler PAI dalam pengembangan keterampilan sosial dan kemandirian siswa MAS - Asmadi, Asmadi; Arlina, Arlina (JPGI (Jurnal Penelitian Guru Indonesia), 2025)
This study aims to explore the extracurricular role of Islamic Religious Education (PAI) in the development of students' social skills and independence at MAS Al-Ittihadiyah Mamiyai Medan. Social skills include the ability to interact with others, which is very important for social life. Through PAI extracurriculars, students not only learn religious aspects, but also social skills such as cooperation, empathy, and communication. In addition, this activity also teaches independence, where students are encouraged to take initiative, manage time, and be responsible. This study uses qualitative methods with literature studies and interviews to analyze the effectiveness of PAI extracurricular in the development of these skills. The results show that this activity has a positive impact on the development of students' social skills and independence, as well as making a significant contribution in shaping their religious character. This research is expected to be the basis for the development of similar programs in other schools.